An Analysis Of Serum Glutamic Pyruvic Transaminase (SGPT) And Serum Glutamic Oxaloacetic Transaminase (SGOT) Drains of Rats (Rattus novergicus) Given Soybean Juice (Glycine max L.) and Zinc: Analysis Of Serum Glutamic Pyruvic Transaminase (SGPT) And Serum Glutamic Oxaloacetic Transaminase (SGOT) Drains of Rats (Rattus novergicus) Given Soybean Juice (Glycine max L.) and Zinc - Muhammad Al Hafidz (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
The liver is the most significant metabolic organ that plays a vital role in the body. The World Health Organisation (WHO) indicates that approximately 20.5 million people die from liver damage. Liver function can be evaluated by measuring the levels of SGPT and SGOT enzymes in the blood. Soy juice and zinc can play a role in maintaining liver health. This study aims to analyze the effect and optimum dose of soybean juice and zinc on the levels of SGPT and SGOT enzymes in the blood of white rats. This study used a completely randomized design (CRD). The control group (K) was only given breast milk and standard rat feed. Treatment 1 (P1) was induced with soybean juice at a dose of 0.6 mL/kgBB, Treatment 2 (P2) was induced with soybean juice and zinc at a dose of 0.6 mL/kgBB, and Treatment 3 (P3) was induced with soybean juice and zinc at a dose of 1.2 mL/kgBB. The data obtained were tested by Analysis of Variance (ANOVA) to determine whether the treatment was significant. Differences were declared significant at p < 0.05 and, after that, continued with a post hoc test (Duncan). The results of this study indicate that the administration of soybean juice (Glycine max L.) and zinc with an optimum dose of 1.2 mL/kgBB provides a significant difference and can keep the levels of SGPT (26 - 61 U/L) and SGOT (39 - 111 U/L) remain normal.